Інституційне середовище капіталізації лісових ресурсів - Голуб, О.А. (Економіка природокористування і охорони довкілля, 2014)
Розглянуто основні аспекти необхідності вирішального вибору стратегічного напрямку (мети) лісокористування – за природозберігаючим чи за промисловим спрямуванням. Визначено, що для першого є набагато більше підстав у рамках існуючої на сьогодні системи соціально-економічних координат. Проаналізовано можливості вибору відповідної сукупності суб’єктів лісокористування, від чого буде в подальшому логічно вибудовуватись вся система економічних та організаційних механізмів у згаданій сфері діяльності. The basic aspects of necessity of a deciding choice of strategic direction (purpose) of forest using – by the nature protection or the industrial direction are considered. It is defined, that for the first, there are much more foundations within the framework of existing system of socio-economic coordinates. The opportunities of choosing an appropriate set of subjects of forest using are analysed, and on its basis, the entire system of economic and organizational mechanisms in this sector of activity will be logically constructed in the future. It is emphasized on necessity of the complex approach when solving forestry problems as a specific kind of activity in specific territories, which have the ecological importance for development of village communities in a context of maintenance of opportunities to increase the ecological standards of the local population life according to the European standards.